Gastric xanthelasma is a warning sign for Helicobacter pylori infection, atrophic gastritis, and intestinal metaplasia - Feng, Lina; Zhang, Mingyu; Guan, Jialun; Zhang, Yu; Huang, Yujie; Dong, Ruonan; Zhao, Kai; Xia, Suhong; Xiao, Fang; Liao, Jiazhi (Frontiers in Medicine, 2023)
Background: Contradictory evidence suggested gastric xanthelasma (GX) was associated with some upper gastrointestinal (GI) diseases. Additionally, no research has been performed on the relationship between esophageal/duodenal xanthelasma and upper GI diseases. Methods: Individuals who underwent esophagogastroduodenoscopy at Tongji Hospital, Tongji Medical College, participated in this retrospective study. This study evaluated whether the risk of GX or esophageal/duodenal xanthelasma was influenced by the following gastroesophageal diseases: superficial gastritis, gastric polyp, bile reflux, peptic ulcer, reflux esophagitis, Barrett's esophagus, esophageal cancer, atrophic gastritis (AG), intestinal metaplasia (IM), dysplasia, gastric cancer, and Helicobacter pylori (H. pylori) infection. Furthermore, subgroup analysis was conducted to establish the relationship between the number of GX and upper GI diseases. Results: Of the 69071 subjects reviewed, 1220 (1.77%) had GX, and 54 (0.08%) had esophageal/duodenal xanthelasma. There was no difference in the prevalence of upper GI diseases between patients with and without esophageal/duodenal xanthelasma. Nevertheless, compared with non-xanthelasma patients, GX patients had a greater proportion of AG, IM, dysplasia, gastric cancer, and H. pylori infection and a lower incidence of superficial gastritis (P<0.05). The multivariate logistic regression analysis indicated AG (OR=1.83, 95%CI: 1.56-2.16), IM (OR=2.42, 95%CI: 2.41-2.85), and H. pylori infection (OR=1.32, 95%CI: 1.17-1.50) were independent risk factors for GX. In addition, patients with multiple GXs had a higher rate of AG and IM than those with single GX. Conclusions: Esophageal/duodenal xanthelasma may not be associated with upper GI diseases, and further research is needed to support this hypothesis. Notably, GX, especially multiple GXs, may be a more easily detected warning sign of AG, IM, or H. pylori infection.